Geochemistry and human health risks of heavy metals in soils from gold mineralized Birimian rocks in Southwestern Burkina Faso - Kadidiatou Coulibaly; Aboubakar Sako (Sustainable Environment)
This study aims to identify sources and health risks of a series of heavy metals in topsoil from Birimian basement rocks in southwestern Burkina Faso. Concentrations of geochemical data of 66 samples were determined using ICP-MS. R-mode factor analysis, Sediment/Soil Quality Guidelines and ecological and human health risk indices were used to investigate the associations between the heavy metals and their impacts on the ecosystem and the local population. It can be noted that 78, 83 and 85% of the samples had maximum concentrations of Ni, Cr and As higher than their respective SQG indices. The mean concentrations of these key contaminants were 42.09, 233.1 and 7.72 mg/kg for Ni, Cr and As, respectively. According to the median effect range mean quotient (MERMQ), 87.9% (MERMQ >0.11) of the samples had 29% probability of being toxic. In contrast, the contamination severity indices (CSI) ranged from 0.17 to 2.11, indicating a very low to moderate probability toxicity. Factor analysis indicated that chemical weathering, with 57% of the total variance, was the dominant factor controlling the soil geochemistry followed by artisanal gold mining (10%) and farming (9%). Thus, weathering was the major contributor to heavy metal loading including Ni, Cr and As. Among heavy metals, only Cr, Ni, As and Ba posed non-cancerogenic (THI >1) and cancerogenic (TCR >1.0 × 10−4) risks to the exposed population with children being the most vulnerable. In the absence of prior knowledge of the soil geochemical status, the heavy metals may be redistributed in the soil environment, and thereby compromising human health.